Bioecology of Simpakolak Fish (Puntius anchisporus) in Empurut River in Entikong Sub-districts, Sanggau Regency - Lestari, Eni; Sirojul, Ahmad Mulyadi; Hurriyani, Yeni (Jurnal Sains Mahasiswa Pertanian, 2020)
Simpakolak fish (Puntius anchisporus) is one of the potential ornamental fish that is not widely known by the public. The development of potential fishery commodities requires a study of fish bioecology one of which includes growth patterns and habitat conditions. This research was conducted in March - June 2020 in Empurut River, Entikong Subdistrict, Sanggau Regency. The total fish caught was 100 fish, consisting of 57 males and 43 females. The growth pattern of simpakolak fish is allometric negative where the value of b = 1.302553185 in male simpakolak fish and value of b = 1.152323795 in female simpakolak fish. (R2) value 0,403 for male and (R2) value 0,531 for female. The results of the analysis of water quality analysis based on physics-chemical parameters indicated that the waters of the Empurut River are in good condition for simpakolak fish habitat. However based on biological parameters, the plankton abundance and diversity are relatively low.Keywords: Puntius anchisporus, Bioecology, growth patterns, habitat conditions.